Maternal health service utilisation of adolescent women in sub-Saharan Africa: a systematic scoping review - Tensae Mekonnen; Tinashe Dune; Janette Perz (BMC, 2019)
Abstract Introduction Sub-Saharan Africa has the highest rate of adolescent pregnancy in the world. While pregnancy during adolescence poses higher risks for the mother and the baby, the utilisation of maternity care to mitigate the effects is low. This review aimed to synthesise evidence on adolescent mothers' utilisation of maternity care in Sub-Saharan Africa and identify the key determinant factors that influence adolescent mothers' engagement with maternity care. Method A systematic review of scholarly literature involving seven databases: ProQuest, PubMed, EMBASE/Elsevier, SCOPUS, PsycINFO, CINAHL and Infomit was conducted. Studies published in English between 1990 and 2017 that examined Sub-Saharan adolescent mothers' experiences of utilising biomedical maternity care during pregnancy, delivery and the post-partum period were included. Results From 296 relevant articles 27 were identified that represent the experience of adolescent mothers' maternal health service utilisation in Sub-Saharan Africa. The review indicates that maternal health service utilisation in the majority of Sub-Saharan African countries is still low. There is also a wide discrepancy in the use of maternity care services by adolescent mothers across countries in Sub-Saharan Africa. Conclusions The review reveals that a significant number of adolescents in Sub-Saharan Africa do not access and use maternity services during pregnancy. Several factors from individual to systemic levels contributed to low access and utilisation. This implies that interventions targeting the women, their partners, healthcare professionals, communities and the organisations (local to national) are necessary to improve adolescent mother's engagement with maternity care in Sub-Saharan Africa.